2011
DOI: 10.1002/uog.9078
|View full text |Cite
|
Sign up to set email alerts
|

Adenoma malignum of the uterine cervix: ultrasonographic findings in 11 patients

Abstract: Objective

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…With large-scale HPV vaccination programs and the projected decrease in the prevalence of HPV-associated adenocarcinomas, there is potential increase in the proportion of gastric type endocervical adenocarcinomas, making early and accurate recognition even more important. Unlike HPV-associated endocervical adenocarcinomas of usual type, gastric type adenocarcinomas, including minimal deviation type, are frequently centered in the upper endocervix, 38 present with a bulky cervix, 39 are usually p16-negative or focal, demonstrate gastric differentiation, and may contain lobular endocervical glandular hyperplasia, its putative precursor. 9,16,23,4043 We presented a more extensive description of the morphologic spectrum of these tumors in abstract form recently (manuscript in preparation) 44 ; we hope this helps pathologists better recognize these distinct tumors.…”
Section: Discussionmentioning
confidence: 99%
“…With large-scale HPV vaccination programs and the projected decrease in the prevalence of HPV-associated adenocarcinomas, there is potential increase in the proportion of gastric type endocervical adenocarcinomas, making early and accurate recognition even more important. Unlike HPV-associated endocervical adenocarcinomas of usual type, gastric type adenocarcinomas, including minimal deviation type, are frequently centered in the upper endocervix, 38 present with a bulky cervix, 39 are usually p16-negative or focal, demonstrate gastric differentiation, and may contain lobular endocervical glandular hyperplasia, its putative precursor. 9,16,23,4043 We presented a more extensive description of the morphologic spectrum of these tumors in abstract form recently (manuscript in preparation) 44 ; we hope this helps pathologists better recognize these distinct tumors.…”
Section: Discussionmentioning
confidence: 99%
“…3 In one case series, ultrasound was able to identify an adenoma malignum in 9 of 11 patients who were later confirmed to have this tumour. 8 Additional features of adenoma malignum in this series included enlargement of the cervix and smooth margins to the cervical mass. A second case series described 13 cases of adenoma malignum and their associated imaging findings.…”
Section: Discussionmentioning
confidence: 71%
“…[2][3][4][5][6] This tumour has also been associated with Peutz-Jeghers syndrome (hereditary intestinal polyposis). [7][8][9] To our knowledge, adenoma malignum presenting with severe electrolyte disturbances has not been previously reported. We describe here the case of a woman with adenoma malignum who presented with profound hyponatremia and hyperkalemia, and we describe the subsequent surgical management.…”
Section: Introductionmentioning
confidence: 87%
“…Park et al . [11] reported that ultrasound imaging with Doppler examination is more efficient and accurate in the evaluation of multilocular lesions of the uterine cervix, and in their study Doppler examination revealed that AM had an increased intralesional vascularity. Recently, magnetic resonance imaging has been shown to be useful for the diagnosis of AM.…”
Section: Discussionmentioning
confidence: 99%